Role of Vitamin D in the Pathogenesis of Inflammatory Bowel Diseases: Literature Review - Anatoly I. Khavkin; Andrew V. Nalyotov; Dmitry I. Masyuta; Ravil F. Makhmutov (Вопросы современной педиатрии)
The pathogenesis of inflammatory bowel diseases still remains unclear nowadays. Genetic disposition, impaired immune regulation, disturbance in intestinal microbiota composition, exposure to environmental factors are associated with the development of inflammation in intestinal mucosa and increased epithelial penetrance that define disease's development and progression. There is a theory in scientific literature that vitamin D deficiency (among other environmental factors) increases the risk of inflammatory bowel disease. However, the role of vitamin D in the development of gastrointestinal tract diseases remains poorly studied. This article presents current data on the vitamin D effect on the intestinal mucosa barrier function, on the immune system and on the intestinal microbiota in the context of inflammatory bowel diseases pathogenesis.